Adoption of NFTs as digital art: The moderating effect of crypto-experience and the role of sustainability - García-Monleon, Fernando; Erdmann, Anett; Arilla Llorente, Ramón; Fernández Hernández, Ruth (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
NFT art objects emerged from blockchain technology and have implied a change in the behaviour, format and understanding of art markets. Given the historical evolution of the technology, following cryptocurrencies and tokenization, this raises the question how the intention to use NFTs relates to the perceived value of cryptocurrency technology. To explore this issue, we set up a partial least square structural equation model. The results identify a positive relationship which is moderated by the crypto-experience of users, becoming weaker as experience grows. Social and environmental sustainability considerations turn out to be fully mediated through the perceived value of cryptocurrencies.